Are renal transplant recipients aware of the necessity of sun protection? - Sułowicz, Joanna; Wojas-Pelc, Anna; Sułowicz, Władysław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Organ transplant recipients are at 10-fold higher risk of developing basal cell carcinoma and up to 250-fold higher risk of developing squamous cell carcinoma compared with the general population. Common risk factors include the type of immunosuppression, fair skin, male gender, older age and sunlight. Objective . To evaluate patients’ compliance with sunlight protection before and after renal transplantation. Material and methods . The study covered 455 patients after renal transplantation aged 18-74 years. A special questionnaire was used to determine age, gender, place of residence, skin type (according to the Fitzpatrick classification), hair and eye colour, and any episodes of sunburn. Outdoor occupation, frequency of sun exposure and residence in a hot climate for a long time were taken into consideration for evaluation of UV exposure. Information about use of sunscreens and protective clothes before and after the renal transplant procedure were also noted. Results . Before the renal transplant procedure only 20% of patients avoided sun at midday (11 am - 4 pm) compared to 64% of patients after renal transplantation. Sunscreens were used by 15.4% vs. 20% and protective clothes 7.7% vs. 21.8% of patients respectively. After the renal transplant procedure 57.6% of patients started to use at least one of the methods of skin cancer prophylaxis. After transplantation 44% of patients (p < 0.01) reported limiting time spent outdoors. 17.1% of patients started to use or used more frequently protective clothes (p < 0.0022) and 14.1% sunscreen creams (p < 0.0315) compared to the situation before the surgical procedure. No sun protection such as protective clothes or sunscreen creams was still used by 78.2% and 80% of patients, respectively. Conclusions . There is insufficient protection against UV light among patients after renal transplantation, so further education is needed.